β-Sitosterol 3-O-D-glucoside increases ceramide levels in the stratum corneum via the up-regulated expression of ceramide synthase-3 and glucosylceramide synthase in a reconstructed human epidermal keratinization model - Takeda, Shogo; Terazawa, Shuko; Shimoda, Hiroshi; Imokawa, Genji (PloS one, 2021)
β-Sitosterol 3- O - d -glucoside (BSG) is known to act as an agonist by binding to estrogen receptors, and estrogen has been reported to enhance the activity of β-glucocerebrosidase, an epidermal ceramide metabolizing enzyme. In this study, we determined whether BSG up-regulates ceramide levels in the stratum corneum (SC) of a reconstructed human epidermal keratinization (RHEK) model. Treatment with BSG significantly increased the total ceramide content by 1.2-fold compared to that in the control in the SC of the RHEK model, accompanied by a significant increase of the ceramide species, Cer[EOS] by 2.1-fold compared to that in the control. RT-PCR analysis demonstrated that BSG significantly up-regulated the mRNA expression levels of serine palmitoyltransferase (SPT)2, ceramide synthase (CerS)3, glucosylceramide synthase (GCS) and acid sphingomyelinase by 1.41–1.89, 1.35–1.44, 1.19 and 2.06-fold, respectively, compared to that in the control in the RHEK model. Meanwhile, BSG significantly down-regulated the mRNA expression levels of sphingomyelin synthase (SMS)2 by 0.87–0.89-fold. RT-PCR analysis also demonstrated that BSG significantly up-regulated the mRNA expression levels of CerS3 and GCS by 1.19–1.55 and 1.20-fold, respectively, but not of SPT2 and significantly down-regulated that of SMS2 by 0.74-fold in HaCaT keratinocytes. Western blotting analysis revealed that BSG significantly increased the protein expression levels of CerS3 and GCS by 1.78 and 1.28–1.32-fold, respectively, compared to that in the control in HaCaT cells. These findings indicate that BSG stimulates ceramide synthesis via the up-regulated expression levels of CerS3 and GCS in the glucosylceramide pathway, which results in a significantly increased level of total ceramides in the SC accompanied by significantly increased levels of acylceramide species such as Cer[EOS].